Applying the Contrastive Linguistic Method to Minimize Javanese Interference in Arabic Language Learning at Islamic Boarding Schools - Gunarti, Tri Tami; Ahmadi, Mubarok; Huda, Nur (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2025)
This study investigates the phonological interference of the Javanese language in Arabic communication among students at Pesantren. Arabic is a medium of instruction and daily communication within the pesantren, yet students’ mother tongue often influences their mastery of Arabic. This qualitative descriptive research identifies and categorizes forms of phonological interference—such as the insertion of non-Arabic phonemes like ta, to, e, seh, and yo—which significantly alter the intended meaning in Arabic discourse. Data were collected through structured observations, interviews, and audio recordings. The findings demonstrate a persistent pattern of phonemic substitution and addition that impacts pronunciation, intonation, and syntactic fluency in Arabic speech. This study reveals the linguistic challenges posed by triglossia and bilingualism in traditional Islamic boarding schools. It provides pedagogical recommendations, including phonological awareness training and the integration of contrastive linguistic methods. These insights are vital for developing more adaptive Arabic language instruction tailored to the linguistic realities of pesantren students, thereby contributing to more effective bilingual education frameworks in Islamic learning institutions